Association Between Age at Menarche and Risk Factors for Cardiovascular Diseases in Korean Women: The 2010 to 2013 Korea National Health and Nutrition Examination Survey. Issue 18 (May 2016) - Won, Jong Chul; Hong, Jae Won; Noh, Jung Hyun; Kim, Dong-Jun
Abstract : Abstract: Early menarche is strongly associated with adulthood obesity; however, the relationship between age at menarche and cardiovascular disease (CVD) in Korean women remains poorly understood. Here, we investigated the association between early menarche and risk factors for developing CVD during adulthood using a nationwide population database. In total, 12, 336 women (weighted n = 17, 483, 406; weighted age, 45.7 years) who participated in the Korean National Health and Nutrition Examination Survey 2010 to 2013 were included in this study. Participants were scored using the National Cholesterol Education Program Adult Treatment Panel III criteria for metabolic syndrome. Risk of CVD was estimated using the 10-year Framingham Coronary Heart Disease Risk Point Scale (10-year FRS). Early menarche (⩽11 years) was reported in 5.2% (weighted n = 917, 493) of subjects. The weighted prevalences of metabolic syndrome and ≥20% 10-year FRS were 23.6% [95% confidence interval (95% CI), 22.7–24.6] and 7.7% (7.1–8.3), respectively. Women with early menarche reported a significantly higher body mass index and waist circumference, along with a higher prevalence of hypertension, diabetes, and metabolic syndrome than those with later menarche (≥13 years). Furthermore, the prevalence of women with a ≥10% or ≥20% 10-year FRS was higher in those with early menarche than in other groups after adjusting for age, smoking, education level, and menstruation. Logistic regression analyses controlling for these and other confounding factors revealed odds ratios of 2.29 (95% CI = 1.25–4.19) and 1.78 (0.96–3.30) for ≥10% and ≥20% 10-year FRS in women with early menarche, respectively, compared with those in the latest menarche group (≥17 years). Taken together, this nationwide study revealed that women with early menarche are at increased risks of metabolic syndrome and CVD. Early menarche may therefore represent an important marker for early preventive interventions.